Homicidio culposo en accidente de trabajo por falta de medidas de seguridad (2016)
Failure of the employer of the obligations of protection and security for staff in charge, entail criminal liability when directly or by delegation orders are generated or protection elements are not provided and an accident in which dies the worker occurs, be committed a crime against life and personal integrity framed in the murder, culpable conduct punishable as a typical result due to lack the objective duty of care and who should have foreseen it brings presents. A considerable number of regulations that do not meet the employer or responsible for the safety of workers, can lead to the occurrence of the fatal event and face trial for manslaughter referred to in Article 109 of the Colombian penal code, a subject on which there are not a significant number of authors who have dealt with but if judgments of the Supreme Court Penal Chamber established in two hierarchical, that superiors recent failures of workers who died in work accidents, were responsible for his death by such reason was convicted of manslaughter, leaving with this an important precedent for employers and staff to this delegated responsibilities of command, note that the existence of a duty stipulated in a labor standards transcends criminal because their ignorance or not application leads to answer a criminal offense